2021
DOI: 10.1016/j.marenvres.2021.105401
|View full text |Cite
|
Sign up to set email alerts
|

The toxic dinoflagellate Alexandrium minutum affects oyster gamete health and fertilization potential

Abstract: Dinoflagellates from the globally distributed genus Alexandrium are known to produce both paralytic shellfish toxins (PST) and uncharacterized bioactive extracellular compounds (BEC) with allelopathic, ichthyotoxic, hemolytic and cytotoxic activities. In France, blooms of Alexandrium minutum appear generally during the spawning period of most bivalves. These blooms could therefore alter gametes and/or larval development of bivalves, causing severe issues for ecologically and economically important species, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have provided a better understanding of the toxicity of A. minutum to bivalves [ 66 , 75 ], with BECs found to be responsible for the negative effects on the gills of adult C. gigas , whereas PSTs impact the digestive gland [ 66 ]. Direct exposure of the early life stages of C. gigas also negatively affected gamete quality, fertilization success, and subsequent larval development [ 16 , 17 , 67 , 74 ], with negative effects attributed primarily to BECs rather than PSTs.…”
Section: Effects Of Bloom Forming Hab Species On Species Of Relevance...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have provided a better understanding of the toxicity of A. minutum to bivalves [ 66 , 75 ], with BECs found to be responsible for the negative effects on the gills of adult C. gigas , whereas PSTs impact the digestive gland [ 66 ]. Direct exposure of the early life stages of C. gigas also negatively affected gamete quality, fertilization success, and subsequent larval development [ 16 , 17 , 67 , 74 ], with negative effects attributed primarily to BECs rather than PSTs.…”
Section: Effects Of Bloom Forming Hab Species On Species Of Relevance...mentioning
confidence: 99%
“…The direct effects of HABs on cultured fish and shellfish species can be substantial and are likely to become more significant considering increasing climate anomalies and as the farmed supply of seafood grows [ 15 ]. The early life stages of cultured species are particularly susceptible to harmful algae and their associated toxic compounds [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Most farmed species are confined and cannot escape blooms.…”
Section: Introductionmentioning
confidence: 99%
“…In the plankton realm, BECs may negatively affect competing protists [58][59][60], immobilise prey [61,62] and predators [4,63], inhibit putative parasites [64], or affect grazing of copepods [65]. Moreover, there is growing evidence that BECs might also be responsible for physiological incapacitation of shellfish [66][67][68][69][70][71][72] or fish [73]. Nevertheless, detailed knowledge on chemical details of the metabolites mediating these interactions is largely lacking.…”
Section: Effects Of Alexandrium On Marine Biotamentioning
confidence: 99%
“…A number of recent studies used a comparative approach with strains that were thoroughly characterised with respect to different bioactive compounds, enabling the distinction between effects from PSTs or BECs (Figure 2). In particular, some of these new studies [66][67][68][70][71][72] exposed bivalve species (M. gigas, Mytilus edulis, Pecten maximus) to different strains of Alexandrium spp., for which PST production and BECs potency (measured as allelochemical or hemolytic potencies) were characterised. These studies clearly highlight that a majority of the deleterious effects observed on bivalves might indeed be due to BECs produced by Alexandrium spp.…”
Section: Toxicity Towards Shellfishmentioning
confidence: 99%